LANGUAGE CHANGE AND DEVELOPMENT: HISTORICAL LINGUISTICS - Trisna Dinillah Harya (Premise: Journal of English Education and Applied Linguistics, 2016)
Language can change and develop by itself slowly. Language can change and development because of adaptation of development and pattern change and system of society life, such as level of education, social, culture and technology mastery. Language change and development can occur internally and externally. In this article the changes internally and language development will be reviewed by looking through the study of historical change and development language based on the history of its development. While changes in external and development will be explored through the study of Sociolinguistics by examining and looking at changes and developments that language is influenced by socio-cultural factors that occur in society. Changes internally initially occurred in the behavior of speakers in their everyday lives to adjust to each other, and followed by a tendency to innovate in groups of people who are already familiar, then followed by other changes in sequence, which ultimately makes a language different each other, although originally derived from a single language family. Changes in the external language change and language development is caused by the contact of a language with other languages, where humans as social beings who have been cultured either interconnected or inter-ethnic nations in the world in a country.